2009
DOI: 10.1128/jb.01605-08
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of NADH:Acceptor Oxidoreductase and Butyryl Coenzyme A Dehydrogenase in Reversed Electron Transport during Syntrophic Butyrate Oxidation by Syntrophomonas wolfei

Abstract: Methanogenic oxidation of butyrate to acetate requires a tight cooperation between the syntrophically fermenting Syntrophomonas wolfei and the methanogen Methanospirillum hungatei, and a reversed electron transport system in S. wolfei was postulated to shift electrons from butyryl coenzyme A (butyryl-CoA) oxidation to the redox potential of NADH for H 2 generation. The metabolic activity of butyrate-oxidizing S. wolfei cells was measured via production of formazan and acetate from butyrate, with 2,3,5-tripheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 40 publications
5
66
0
Order By: Relevance
“…A link between a low [NAD ϩ ]/[NADH] ratio and the stimulation of ␤-oxidation was observed previously (8,9). Furthermore, participation of an NADH:acceptor oxidoreductase as a physiological partner of a butyryl-CoA dehydrogenase was recently proposed in Syntrophomonas wolfei, although the enzyme was not identified (54).…”
Section: Exx(t//s)xlhxrxhxn(t/s)xr(v/i)mentioning
confidence: 99%
“…A link between a low [NAD ϩ ]/[NADH] ratio and the stimulation of ␤-oxidation was observed previously (8,9). Furthermore, participation of an NADH:acceptor oxidoreductase as a physiological partner of a butyryl-CoA dehydrogenase was recently proposed in Syntrophomonas wolfei, although the enzyme was not identified (54).…”
Section: Exx(t//s)xlhxrxhxn(t/s)xr(v/i)mentioning
confidence: 99%
“…Since the redox potential of the H + /H 2 pair and the CO 2 /formate pair at pH 7.0 are nearly identical (E 0 ' = −414 vs. −430 mV) and most methanogenic partners can use both hydrogen and formate as electron donors, it has remained a matter of discussion whether actually hydrogen or formate is the electron carrier between secondary fermenters and their methanogenic partners (Bryant et al 1967;McInerney et al 1979). Recent evidence obtained in biochemical, genomic, and proteomic studies of secondary fermenters indicates that formate may be at least as important as hydrogen in interspecies electron transfer (Müller et al 2009;Müller et al 2010;Schmidt et al 2013;Worm et al 2011). We therefore included measurement of formate pool sizes in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In only few of these studies, hydrogen partial pressures could be measured with reliable methods (e.g., (Pauss et al 1990)), and measurement of formate at micromolar concentrations was not possible at all so far. However, recent studies on the biochemistry of syntrophic oxidations (Müller et al 2009;Müller et al 2010;Schmidt et al 2013;Worm et al 2011) have shown that formate may be at least as important as hydrogen as an electron carrier between syntrophic partners. For a more exact assessment of the energetic situation of the various trophic groups within the biogas-forming community, we measured in the present study pool sizes of fatty acids including formate and of hydrogen and carbon monoxide at high sensitivity in digesting sludge from four different digesters operating at different rates with different feeds and efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…The volume of biogas was measured by gas measurement collector, while the biogas content, volatile fatty acids (VFAs) and ethanol were determined by gas chromatography [19]. The dehydrogenase activity of the activated sludge was detected using iodonitrotetrazolium chloride (INT) [20,21].…”
Section: Analysis and Detection Methodologymentioning
confidence: 99%